The impact of audit quality on firm performance: evidence from Malaysia - Sayyar, Hamed (2015)
Nowadays in the emerging market and after corporate scandals as well as financial crisis the issue of firm performance and ways to improve it are crucial for companies, investors and third parties. One of the ways that it can impact firm performance is audit quality, which it is recognize as external monitoring. Therefore, the purpose of this research is to examine the impact of audit quality on firm performance for Malaysian listed companies for the period of 2003 to 2012. In this study, we use audit fees and audit firm rotation as proxies for audit quality. Return on assets and Tobin’s q are used as measures for firm performance. We found that there is insignificant relationship between audit quality proxies (audit fees and audit firm rotation) and ROA. We also found that an audit fee is significantly and positively related to Tobin’s Q. However, audit firm rotation is insignificantly related to Tobin’s Q.